2017
DOI: 10.3389/fnagi.2016.00316
|View full text |Cite
|
Sign up to set email alerts
|

Blood Beta-Amyloid and Tau in Down Syndrome: A Comparison with Alzheimer’s Disease

Abstract: Background: Changes in β-amyloids (Aβ) and tau proteins have been noted in patients with Alzheimer’s disease (AD) and patients with both Down syndrome (DS) and AD. However, reports of changes in the early stage of regression, such as behavioral and psychological symptoms of dementia (BPSD), in DS are sparse.Methods: Seventy-eight controls, 62 patients with AD, 35 with DS and 16 with DS with degeneration (DS_D), including 9 with BPSD and 7 with dementia, were enrolled. The levels of β-amyloids 40 and 42 (Aβ-40,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
58
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 30 publications
10
58
1
1
Order By: Relevance
“…Exposure of RBCs exposed to Aβ on the luminal surface of cerebral microvessels induces the erythrocytes' adhesion to endothelial cells and affects endothelial functionality [68] [69]. In agreement with these notions, Down syndrome patients with elevated Aβ levels in blood plasma were reported to have a greater risk of developing AD [70,71].…”
Section: Aβ-induced Morphological Changes In Erythrocytessupporting
confidence: 69%
See 2 more Smart Citations
“…Exposure of RBCs exposed to Aβ on the luminal surface of cerebral microvessels induces the erythrocytes' adhesion to endothelial cells and affects endothelial functionality [68] [69]. In agreement with these notions, Down syndrome patients with elevated Aβ levels in blood plasma were reported to have a greater risk of developing AD [70,71].…”
Section: Aβ-induced Morphological Changes In Erythrocytessupporting
confidence: 69%
“…Four modified morphologies of RBCs triggered by Aβ binding were suggested to indicate AD progression [69]. In agreement with these notions, Down syndrome patients with elevated Aβ levels in blood plasma were reported to have a greater risk of developing AD [70,71].…”
Section: Aβ-induced Morphological Changes In Erythrocytessupporting
confidence: 64%
See 1 more Smart Citation
“…The Aβ1:42:Aβ1‐40 ratio itself has been shown to be higher among individuals with DS as compared to healthy controls (Iulita et al, ; Matsuoka et al, ). This ratio was also found to be higher among those with DS and AD dementia as compared to those without dementia (Head et al, ; Iulita et al, ; Lee et al, ; Matsuoka et al, ). Among ApoeE4 carriers and non‐carriers, higher concentrations of the Aβ1‐42:Aβ1‐40 ratio were identified among those individuals who have been diagnosed with AD dementia for over 4 years relative to those with less than 4 years since diagnosis (Prasher, Sajith, Mehta, Zigman, & Schupf, ).…”
Section: Resultsmentioning
confidence: 91%
“…Similar to Aβ1‐42, conflicting results have been shown for plasma Aβ1‐40 with some studies unable to identify a link between DS and AD dementia (Schupf et al, ) while other studies have shown elevated levels (Coppus et al, ; Fortea et al, ; Head et al, ; Iulita et al, ) or decreased levels (Lee et al, ). The link between plasma Aβ1‐40 concentrations among individuals with DS and AD dementia may be less dependent on APOEe4 carrier status as both higher rates have been found among APOEe4 carriers as well as non‐carriers (Head et al, ; Matsuoka et al, ).…”
Section: Resultsmentioning
confidence: 99%